SMART FISH POND MONITORING DAN CONTROLLING INTERNET OF THINGS (IOT) IKAN HIAS (STUDY KASUS : DINAS KELAUTAN DAN PERIKANAN PROVINSI JAMBI): Cultivation;Feed;Internet of Things (IOT);NodeMCU ESP8266;Web. - Yeniwati, Desi; Nilawati; Mawardi (FORTECH (Journal of Information Technology), 2021)
Feed is a source of energy for the growth and life of living things. In fish farming, the fish feed formula must meet the nutritional needs of the cultivated fish. The purpose of this research is to design a device that can help alleviate the provision and control of fish feed. This device can give a sign that the food supply is running low, so that it can make it easier for employees in the Telaipura Ornamental Fish Installation to provide fish food. This device is based on the Internet of Things (IOT), one of the Internet of Things (IOT) devices is a monitoring or controlling system that uses sensors and actuators in a certain environment such as a website. The main controller used is NodeMCU ESP8266. Activities in the form of scheduling fish feed can be arranged, weight expenditure of fish feed can be arranged and monitoring of feeding can be seen through the web that has been made. The HCSR04 sensor is used as whether the feed is still there or has run out, it is equipped with a notification LED visualized through the dashboard on the web. With this tool, ornamental fish cultivators can increase crop production due to reduced maintenance costs for heavy feeding, maintenance time becomes more efficient and monitoring of feed expenditure can be monitored.